Durability development of lightweight and high-strength engineered cementitious composites subject to combined sulfate–chloride attack under freeze–thaw cycles - Gou, Hongxiang; Sofi, Massoud; Zhang, Zipeng; Zhu, Hongbo; Zhu, Mintao; Mendis, Priyan (Construction & building materials, 2023)
•A novel lightweight and high-strength engineered cementitious composite was developed.•The deterioration degree of salt solutions on tensile properties of LECC was LECC-S > LECC-CS > LECC-C.•The external sulfate–chloride environment under low temperature offered highly suitable conditions for the formation of expansive thaumasite.•The combined physical and chemical attacks of sulfate promoted chloride diffusion, but chloride ion delayed sulfate’s diffusion and expansion reaction. A novel lightweight high-strength engineered cementitious composite (LECC) was developed, and its mechanical property changes and the resultant durability evolution under the triple coupling factors of chloride attack, sulfate attack, and freeze–thaw cycles were studied. The results indicate that the salt solutions can accelerate the failure of LECC under freeze–thaw cycles. Salt solutions accelerated the tensile properties degradation of LECCs, and the deterioration degree was LECC-S (sulfate) > LECC-CS (chloride-sulfate) > LECC-C (chloride). The influence degree of salt solutions on mass loss was LECC-CS > LECC-C > LECC-S, while their influence on relative dynamic elastic modulus was LECC-S > LECC-CS > LECC-C. The surface spalling and internal structure destruction of LECC after salt freezing provided a favorable channel for CO2 penetration in the environment and the external sulfate–chloride environment under low temperature offered highly suitable conditions for the formation of expansive thaumasite. The combined physical and chemical attacks of sulfate promoted chloride diffusion, but chloride ion delayed sulfate’s diffusion and expansion reaction. This study more comprehensively revealed the durability development of LECC in some abominable environments and provided data support for the engineering application of LECC.